Remarkable Rhinophoridae in a growing generic genealogy (Diptera: Calyptratae, Oestroidea). (2nd June 2014) - CERRETTI, PIERFILIPPO; LOGIUDICE, GIUSEPPE; PAPE, THOMAS
Abstract Four new genera (Apomorphytogen.n. from Costa Rica, Bixiniagen.n. from Australia, Rhinodoniagen.n. from New Caledonia, Rhinopezagen.n. from Papua New Guinea) and nine new species (Apomorphyto inbiosp.n., Bixinia collessisp.n., B. solitariasp.n., B. speisp.n., B. variabilissp.n., B. winklerisp.n., Rhinodonia antiquasp.n., R. flavicerasp.n., Rhinopeza gracilissp.n.) of Rhinophoridae (Diptera: Calyptratae, Oestroidea) are described. All new species were included in a morphology‐based phylogenetic analysis to provide arguments for the justification and monophyly (when nonmonotypic) of the new genera and for including these in the Rhinophoridae. The New Caledonian Rhinodonia is a candidate sister taxon to all other rhinophorids, and the Australasian 'axiniine' species emerge inside a clade of all Neotropical taxa thus suggesting migration from South America across Antarctica into Australia. This published work has been registered in ZooBank, http://zoobank.org/urn:lsid:zoobank.org:pub:51C1F448‐DDD0‐4F14‐8173‐B8C687F7E841.